Al-Haya’ Instrument Construction: Shame Measurement Based on the Islamic Concept - Lisya Chairani; Hijriyati Cucuani; Suwanda Priyadi (Jurnal Psikologi Islam dan Budaya, 2021)
Shame is a noble character in Islam. This study aimed to develop an instrument to measure the Islamic concept of shame (Al-Haya’). The concept used in this study is grounded by Al-Haya’ concept from Alquran and Hadith. The scale was tested on 308 adult Muslims in Pekanbaru. The data analyzed using the Rasch Model. The result demonstrated that 38 items have fulfilled the fit criteria. Exploratory factor analysis resulted in 16 items grouped into five factors about shame against religious values, verbal violations, refusing to worship, inappropriate behavior, and shame of right violations. Furthermore, to find out the validity, The Al-Haya' scale was correlated with a self-control scale (SCS). The Al-Haya’ scale and SCS have alpha .875 and .842, respectively. Al-Haya’ scale has correlation to full SCS (r =.345) and brief SCS (r =.333). It demonstrated that the scale can be used to measure the shame of Muslim.